Enhancement of dielectric performance upto GHz of the composites with polymer encapsulated hybrid BaTiO3–Cu as fillers: multiple interfacial polarizations playing a key role. Issue 43 (13th April 2016) - Li, Chengliang; Yu, Shuhui; Luo, Suibin; Yang, Wenhu; Ge, Zaochuan; Huang, Haitao; Sun, Rong; Wong, Ching-Ping
Abstract : Cu nanoparticles with diameters of 15–25 nm were grown discretely on the surface of BaTiO3 (about 100 nm) via a hydrothermal method, and a polyethylene glycol 4000 (PEG-4000) layer was coated on the surface of the obtained BT–Cu hybrid particles. Abstract : Cu nanoparticles with diameters of 15–25 nm were grown discretely on the surface of BaTiO3 (about 100 nm) via a hydrothermal method, and a polyethylene glycol 4000 layer was coated on the surface of the obtained BT–Cu hybrid particles. The PEG layer will serve as a robust interface layer to suppress the mobilization of charge carriers and protect Cu from oxidation. The BT–Cu particles were loaded as fillers in the matrix of polyvinylidene fluoride (PVDF) to fabricate the BT–Cu/PVDF composites. Microstructure and dielectric performance have been investigated. The results showed that the relative permittivity ( ε r ) of the composites increased prominently with the loading amount and meanwhile the dielectric loss tangent was suppressed at a low level. For instance, the permittivity of BT–Cu/PVDF with the volume fraction of 53.7% reached 150 with a low loss of 0.16 at 1 kHz. The permittivities maintained high values of over 55 and the dielectric loss was less than 0.05 upto 1 GHz. Investigation on the polarization mechanisms has been conducted and the interfacial polarization between different phases should account for the high dielectric permittivity upto GHz. The energy storage characteristics were also studied.